Christian Understandings of Christ : The Historical Trajectory - Jensen, David Hadley, 1968- (Christian understandings., 2019)
Seeing the contours of Christian thought about Christ. Throughout the two-thousand-year span of Christian history, believers in Jesus have sought to articulate their faith and their understanding of how God works in the world. How do we, as we examine the vast and varied output of those who came before us, understand the unity and the diversity of their thinking? How do we make sense of our own thought in light of theirs? The Christian Understandings series offers to help. In this insightful volume, David H. Jensen offers an engaging tour through more than two millennia of thought on Christ. Starting with the New Testament and moving forward, Jensen outlines the myriad beliefs, developments, and questions encompassing the attempts to understand Christianity's most central--and most mysterious--figure. From the patristic portrayals to medieval Christology, from the Reformation to the Enlightenment, and into the twentieth century and beyond, Jensen presents a helpful and needed guide.